Neuromuscular Electrical Stimulation (NMES) as an Add-on Therapy for the Improvement of Dyspnea in Patients with Post-Covid Syndrome: a Protocol for a Phase II Randomized, Non-Pharmacological Intervention-Controlled, Double-Blind Study. (Principles and Practice of Clinical Research, 2022)
Introduction: To date, 501 million people have been infected with SARS-CoV-2, and the incidence of COVID-19 is still increasing as new variants develop. Beyond the well-known short-term consequences of morbimortality of the COVID-19 disease, multiple long-term sequelae have been identi-fied, which are referred to as Post COVID Syndrome (PCS). Dyspnea beyond three weeks from in-fection is the most common long-term symptom, and physical therapy is the standard care for those patients. Neuromuscular Electrical Stimulation (NMES) has been previously used to improve muscle weakness in different pulmonary diseases with promising results. Therefore, given the expected burden of disease, additional tools that seek to optimize patient care, which are easy to use and cost-effective, are a promising approach to PCS recovery. Objective: To compare the efficacy of NMES plus physical therapy against sham procedure and physical therapy in improving dyspnea among patients who developed PCS.Methods: This trial will be a multicentric randomized sham-controlled, double-blinded parallel phase 2 superiority trial. Patients admitted to the hospital with moderate to severe COVID-19, who develop PCS, will be allocated to intervention and sham groups in a 1:1 ratio. They will be assessed for dyspnea through the 6-minute walk test (6MWT) for three months.Conclusion: To our knowledge, no previous published literature tested the same intervention array as this study. Thus, the study assesses the possible impact of the proposed intervention to improve dyspnea among patients with PCS.Keywords: COVID-19, Post-COVID Syndrome, Post-acute COVID, Long COVID, Neuromuscular Electrical Stimulation, Dyspnea.